Surface and subsurface dispersal of radioactive materials from Fukushima by subpolar gyre and intermediate waters in the North Pacific - Seung-Tae Lee; Yang-Ki Cho; Jihun Jung; Seunghwa Chae (Scientific Reports, 2024)
Abstract Radioactive materials were released into the ocean following the Fukushima Daiichi Nuclear Power Plant accident in 2011. Six years after the accident, the radioactive material concentration was markedly increased in the Okhotsk Intermediate Water (OIW) of the Sea of Okhotsk. This material may have been subjected to southward subsurface dispersal by the North Pacific Intermediate Water (NPIW), which originates from the OIW. The spatiotemporal limitations of available methods have made it challenging to track the dispersal paths of radioactive materials in the North Pacific Subpolar region. Here, we performed a tracer experiment using a three-dimensional numerical model to determine the path of 137Cs from Fukushima to the Sea of Okhotsk via surface subpolar gyre currents and subsurface dispersion by OIW and NPIW. The results showed that the 137Cs concentration in the Sea of Okhotsk increased via the surface current and moved progressively southward via OIW six years after the accident and eastward via OIW and NPIW nine years after the accident, indicating that 137Cs transported by NPIW entered the subtropical region. Based on experiments, this temporal change was mainly caused by ocean currents. Thus, subsurface recirculation of radioactive material via the OIW and NPIW should be considered based on the predicted path and travel time of additional materials released from the power plant.